The impact and public health response of chiropractors to the COVID-19 pandemic: a survey across four continents - Craig Moore; Arnold Y. L. Wong; Katie de Luca; Diana De Carvalho; Melker S. Johansson; Katherine A. Pohlman; Amy Miller; Martha Funabashi; Paul Dougherty; Simon French; Jon Adams; Greg Kawchuk (Chiropractic & Manual Therapies, 2022)
Abstract Background The unprecedented impact of COVID-19 on healthcare professionals has implications for healthcare delivery, including the public health guidance provided to patients. This study aims to assess the response and impact of COVID-19 on chiropractors internationally, and examines the public health response of chiropractors to the COVID-19 pandemic practising under a musculoskeletal spine-care versus subluxation-based care paradigm. Methods A survey was distributed to chiropractors in Australia, Canada, Denmark, Hong Kong, United Kingdom and United States (Oct. 2nd–Dec. 22nd, 2020) via professional bodies/publications, and social media. Questions were categorised into three domains: socio-demographic, public health response and business/financial impact. Multivariable logistic regression explored survey items associated with chiropractors practising under different self-reported paradigms. Results A total of 2061 chiropractors representing four global regions completed the survey. Our recruitment method did not allow the calculation of an accurate response rate. The vast majority initiated COVID-19 infection control changes within their practice setting, including increased disinfecting of treatment equipment (95%), frequent contact areas (94%) and increased hand hygiene (94%). While findings varied by region, most chiropractors (85%) indicated that they had implemented regulator advice on the use of personal protective equipment (PPE). Suspension of face-to-face patient care during the peak of the pandemic was reported by 49% of the participants with 26% implementing telehealth since the pandemic began. Chiropractors practising under a musculoskeletal spine-care paradigm were more likely to implement some/all regulator advice on patient PPE use (odds ratio [OR] = 3.25; 95% confidence interval [CI]: 1.57, 6.74) and practitioner PPE use (OR = 2.59; 95% CI 1.32, 5.08); trust COVID-19 public health information provided by government/World Health Organisation/chiropractic bodies (OR = 2.47; 95% CI 1.49, 4.10), and initiate patient telehealth in response to COVID-19 (OR = 1.46; 95% CI 1.02, 2.08) compared to those practising under a subluxation-based paradigm. Conclusions Chiropractors who responded to our survey made substantial infectious control changes in response to COVID-19. However, there was regional variation in the implementation of the advised practitioner and patient use of PPE and limited overall use of telehealth consultations by chiropractors during COVID-19. Musculoskeletal spine-care chiropractors were more adaptive to certain COVID-19 public health changes within their practice setting than subluxation-based chiropractors.